Two further patients with Warsaw breakage syndrome. Is a mild phenotype possible? - Bottega, Roberta (Mol Genet Genomic Med, 2019)
BACKGROUND: Warsaw Breakage Syndrome (WABS) is an ultra rare cohesinopathy caused by biallelic mutation of DDX11 gene. It is clinically characterized by pre and postnatal growth delay, microcephaly, hearing loss with cochlear hypoplasia, skin color abnormalities, and dysmorphisms. METHODS: Mutational screening and functional analyses (protein expression and 3D‐modeling) were performed in order to investigate the presence and pathogenicity of DDX11 variant identified in our patients. RESULTS: We report the clinical history of two sisters affected by WABS with a pathological mytomicin C test carrying compound heterozygous mutations (c.2507T > C / c.907_920del) of the DDX11 gene. The pathogenicity of this variant was confirmed in the light of a bioinformatic study and protein three‐dimensional modeling, as well as expression analysis. CONCLUSION: These findings further extend the clinical and molecular knowledge about the WABS showing a possible mild phenotype without major malformations or intellectual disability.